Team Bear Versus Tiger : An Analysis of the Use and Role of Emojis in a K-pop Fan Community - Haapala, Hanna (My University, 2026)
This thesis analyses how emoji use facilitates belonging and membership within a K-pop fan community. Its aim is to outline typical emoji practices in the context of fan-created language and show how these practices contribute to gaining membership. The data come from posts on X made by fans of the group BTS which include emojis or discussion about the emojis associated with the band. Drawing on the Community of Practice framework, the analysis views learning a social event and demonstrates how the emoji practices serve multiple functions from shorthand referencing to signalling membership. The findings reveal an emoji competence which is not only crucial for engagement within the community but also actively promoted to newcomers by more experienced members. Overall, the study indicates that emojis serve a complex role in the construction and maintenance of a global community. This thesis has important implications for community specific emoji research.
Keywords: digital language; emojis; fan community; community of practice; social media posts